Transportasi Angkot Rute Sarilamak-Kota Payakumbuh - Yuana Canabisfa; Zul Asri (Jurnal Kronologi, 2022)
Abstract This research is one of the historical studies that discusses the development of the Sarilamak - Payakumbuh public transportation route in 2004-2020. The purpose of the study was to explain the changes that occurred in the angkottransportation on the Sarilamak-Payakumbuh route that occurred from 2004 to 2020 with the transfer of the capital city of Lima Puluh Kota Regency to Sarilamak and how it affected the angkot drivers. This study uses historical research methods with the following steps: (1) Heuristics, (2) Source Criticism, (3) Interpretation of data, (4) Historiography. The results of this study indicate that the angkot on the Sarilamak-Payakumbuh route has developed as the main public transportation tool for the community from 2004-2014. Angkot experienced a setback in 2015-2020. The cause of the decline in public transportation has made people start switching to private vehicles as a means of transportation because it is easier to get personal transportation. And in 2020, a government regulation regarding road restrictions was issued on a large scale due to the development of the covid-19 virus which had an impact on reducing the number of angkot on the Sarilamak-Kota Payakumbuh route and angkot drivers who switched professions because the operational burden was not commensurate with income. The impact that occurs due to the decline of angkot makes angkot drivers lose their jobs and switch to other jobs. Keywords: Public Transportation, Transportation, Route Abstrak Penelitian ini merupakan salah satu kajian sejarah yang membahas tentang Perkembangan Angkot Rute Sarilamak – Kota Payakumbuh Tahun 2004-2020. Tujuan Penelitian untukmenjelaskan tentang perubahan yang terjadi pada transportasiangkot rute Sarilamak-Kota Payakumbuh yang terjadi Tahun2004 sampai 2020 dengan adanya perpindahan ibukotaKabupaten Lima Puluh Kota ke Sarilamak dan bagaimanadampaknya terhadap sopir angkot. Penelitian inimenggunakan metode penelitian sejarah dengan Langkah-langkah sebagai berikut : (1) Heuristik, (3) Interpretasi dan (4) Historiografi. Hasil penelitian ini menunjukan bahwa AngkotRute Sarilamak-Kota Payakumbuh mengalami perkembangansebagai alat transportasi umum utama masyarakat dari tahun2004-2014. Angkot mengalami kemunduran pada tahun 2015-2020. Penyebab dari kemunduran angkot membuatmasyarakat mulai beralih ke kendaraan pribadi sebagai alattransportasi karena lebih mudah mendapatkan alat transportasipribadi. Dan pada tahun 2020 dikeluarkannya peraturanpemerintahan tentang pembatasan jalan secara besar-besaranakibat berkembangnya virus covid-19 yang berdampak pada berkurangnya jumlah angkot di rute Sarilamak-Kota Payakumbuh dan sopir angkot yang beralih profesi karenabeban operasional yang tidak sebanding dengan pendapatan.Dampak yang terjadi akibat kemunduran angkot membuatsopir angkot kehilangan pekerjaan dan beralih ke pekerjaanlain.